Measurement of pressures up to 7 MPa applying pressure balances for dielectric-constant gas thermometry. (19th August 2015) - Zandt, Thorsten; Sabuga, Wladimir; Gaiser, Christof; Fellmuth, Bernd
Abstract: For the determination of the Boltzmann constant by dielectric-constant gas thermometry, the uncertainty of pressure measurements in helium up to 7 MPa has been decreased compared with previous achievements (Sabuga 2011 PTB-Mitt .121 247–55). This was possible by performing comprehensive cross-float experiments with a system of six special pressure balances and the synchronization of their effective areas. It is now possible to measure a helium pressure of 7 MPa with a relative standard uncertainty of 1.0 ppm applying a 2 cm 2 piston-cylinder unit, the calibration of which is traceable to the SI base units.